Revealing Factors Affecting Supply Chain Performance of Food and Beverage PT. Sriboga Marugame Indonesia - Evita Tri Handayani; Dedi Fardiaz (ARKA INSTITUTE, 2023)
Studies related to SCM have been conducted, but the relationship between competitive advantage and supply chain performance remains to be determined today, and the explanation of to what extent information technology affects competitive advantage within the supply chain needs to be clarified. This study intends to research how supply chain performance influences the logistics performance and company performance of PT. Sriboga Marugame Indonesia as an F&B company. This study uses a quantitative approach with an explanatory design with PT Sriboga Marugame Indonesia employees as the population. The saturated sample technique was used as the population of 97 respondents was limited and could be reached by the researcher. The data analysis method uses PLS-SEM with Smart PLS program version 3.2.9. The research finds that both supply chain management and logistic performance have a significant effect on organizational performance. Moreover, information technology moderates the relationship between supply chain management and organizational performance. However, the impact of logistic performance on organizational performance was unaffected by information technology. The outcome of this study will help PT Sriboga Marugame Indonesia management to enlighten more about the benefit of Information Technology advancement, especially in supply chain management and logistics.